ANALISIS HARGA DAN KUALITAS PELAYANAN DALAM MENENTUKAN LOYALITAS PELANGGAN PADA ARNOLD GYM DI BONDOWOSO MELALUI KEPUASAN KONSUMEN SEBAGAI VARIABEL INTERVENING - Putra, Virai Mandia; Soeliha, Siti; Pramesthi, Riska Ayu (Fakultas Ekonomi dan Bisnis, 2023)
Marketing is a total system of business activities designed to satisfy consumer needs. Arnold Gym is currently required to provide other needs that support the development of this business in the future. Arnold Gym is a place of business engaged in services that provides places and facilities to do sports that are oriented towards health. The purpose of this study was to analyze and test price analysis and service quality in determining customer loyalty at Arnold Gym in Bondowoso through consumer satisfaction as an intervening variable. This research is a quantitative method research. The population in this study are consumers of Arnold Gym. The sampling technique is determined by quota sampling. Data analysis and hypothesis testing in this study used the Structural Equation Model - Partial Least Square (PLS-SEM). The results of the direct effect hypothesis test using the Smart PLS 3.0 application, show that the price variable has a significant positive effect on customer satisfaction, service quality has a significant positive effect on customer satisfaction, price has a significant positive effect on customer loyalty, service quality has a significant positive effect on customer loyalty, Consumer satisfaction has a significant positive effect on customer loyalty. The results of the indirect effect hypothesis test show that the price variable on customer loyalty through customer satisfaction has a significant positive effect, service quality on customer loyalty through customer satisfaction has a significant positive effect.